Qaeda al-Yaqinu Laa Yuzaalu Bisyak and its Implementation in Fiqh Law - Faridz Anwar, Ahmad Faridz Anwar1; Djumhur Salikin, Adang (Ann Publisher, 2023)
The fundamentals of Islamic law, or usul fiqh, must be learned as part of the fiqh study process. Al-Yaqinu Laa Yuzaalu Bisyak, which translates to